A Cross-Layer-Based Routing Protocol for Ad Hoc Cognitive Radio Networks. (4th October 2015) - Joshi, Gyanendra Prasad; Nam, Seung Yeob; Kim, Chang-Su; Kim, Sung Won
Abstract : This paper proposes a cross-layer-based routing protocol for mobile ad hoc cognitive radio networks. The routing layer receives the spectrum-availability-related information from the medium access control layer and selects the next hop node on the route according to the spectrum information. This paper examines the expectation of channel switching in a range of scenarios and proposes a novel route selection method to mitigate the frequent channel switching. The proposed protocol distributes the routing overheads among secondary users in the network and prolongs the network lifetime. An extensive simulation was performed to evaluate the proposed approach, and the results showed that the proposed protocol extends the network lifetime and maintains a higher data delivery ratio.